A cross-sectional study of blood cultures and antibiotic use in patients admitted from the Emergency Department: missed opportunities for antimicrobial stewardship. Issue 1 (December 2016) - Shallcross, Laura; Freemantle, Nick; Nisar, Shasta; Ray, Daniel
Abstract Background Early review of antimicrobial prescribing decisions within 48 h is recommended to reduce the overall use of unnecessary antibiotics, and in particular the use of broad-spectrum antibiotics. When parenteral antibiotics are used, blood culture results provide valuable information to help decide whether to continue, alter or stop antibiotics at 48 h. The objective of this study was to investigate the frequency of parenteral antibiotic use, broad spectrum antibiotic use and use of blood cultures when parenteral antibiotics are initiated in patients admitted via the Emergency Department. Methods We used electronic health records from patients admitted from the Emergency Department at University Hospital Birmingham in 2014. Results Six percent (4562/72939) of patients attending the Emergency department and one-fifth (4357/19034) of those patients admitted to hospital were prescribed a parenteral antimicrobial. More than half of parenteral antibiotics used were either co-amoxiclav or piperacillin-tazobactam. Blood cultures were obtained in less than one-third of patients who were treated with a parenteral antibiotic. Conclusions Parenteral antibiotics are frequently used in those admitted from the Emergency Department; they are usually broad spectrum and are usually initiated without first obtaining cultures. Blood cultures may have limited value to support prescribing review as part of antimicrobial stewardship initiatives.